2021
DOI: 10.3389/fcell.2021.679046
|View full text |Cite
|
Sign up to set email alerts
|

ARF GTPases and Their Ubiquitous Role in Intracellular Trafficking Beyond the Golgi

Abstract: Molecular switches of the ADP-ribosylation factor (ARF) GTPase family coordinate intracellular trafficking at all sorting stations along the secretory pathway, from the ER-Golgi-intermediate compartment (ERGIC) to the plasma membrane (PM). Their GDP-GTP switch is essential to trigger numerous processes, including membrane deformation, cargo sorting and recruitment of downstream coat proteins and effectors, such as lipid modifying enzymes. While ARFs (in particular ARF1) had mainly been studied in the context o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 73 publications
1
50
0
Order By: Relevance
“…Elegant in vitro studies have shown that a VAPA-OSBP complex is sufficient to transfer cholesterol and PtdIns(4) P in vitro between vesicles (de la Mora et al, 2021). In living cells, this process in addition requires ARF1 that, by cycling between its GDP and GTP-bound forms, contributes to the recruitment of OSBP at the ER-Golgi MCSs (Adarska et al, 2021; Donaldson et al, 2005; Nakatsu & Kawasaki, 2021). The mechanism that ensures initial recruitment of ARF1 at MCSs is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant in vitro studies have shown that a VAPA-OSBP complex is sufficient to transfer cholesterol and PtdIns(4) P in vitro between vesicles (de la Mora et al, 2021). In living cells, this process in addition requires ARF1 that, by cycling between its GDP and GTP-bound forms, contributes to the recruitment of OSBP at the ER-Golgi MCSs (Adarska et al, 2021; Donaldson et al, 2005; Nakatsu & Kawasaki, 2021). The mechanism that ensures initial recruitment of ARF1 at MCSs is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between Vps13 and the Golgi membranes could also be established through Golgi-specific lipids. Purified Vps13 binds well to liposomes containing PI(4)P, the lipid produced and enriched in Golgi membranes [65,66]; the N-terminal region of Vps13 is responsible for this interaction [22]. We recently demonstrated that Vps13 and VPS13A possess the APT1 domain [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Type II ARFs ARF1 and ARF3 are the sole ARFs localizing to TGN membranes After establishing the role of different ARFs in sorting at early secretory organelles, we next wanted to test their role in export from the TGN. As all ARFs have been implicated in post-Golgi trafficking (Adarska et al, 2021) we set out to understand which ones localize to the most distal TGN cisternae and to investigate their spatial relationship with the clathrin machinery. Firstly, the localization of the different ARF members endogenously tagged with 2xALFA was tested with the TGN marker Golgin97.…”
Section: Different Arf Isoforms Support Copi Recruitment On Different...mentioning
confidence: 99%